The Hudson Primer : The Ecology of an Iconic River - Strayer, David Lowell, 1955- (Book collections on Project MUSE., 2012)
This succinct book gives an intimate view of the day-to-day functioning of a remarkable river that has figured prominently in history and culture-the Hudson, a main artery connecting New York, America, and the world. Writing for a wide audience, David Strayer distills the large body of scientific information about the river into a non-technical overview of its ecology. Strayer describes the geography and geology of the Hudson and its basin, the properties of water and its movements in the river, water chemistry, and the river's plants and animals. He then takes a more detailed look at the Huds.